After posting this problem I spent some of my time on the difference of zeroes of quadratic polynomial and came to the following result:
Consider a polynomial f(x)=x2−bx+a and suppose it's roots are p and q and you know the value k where
p−q=k. Then b2−4a=k2
Proof:
f(x)=x2−bx+a
From Vieta's formula
p+q=b
and
pq=a
as, p−q=k therefore p=q+k
putting this in above equations
2q+k=b
and
q2+qk=a
b2−4a=(2q+k)2−a(q2+qk)=4q2+4qk+k2−4q2−4qk=k2
#Algebra
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
There are no comments in this discussion.